Azure cloud security for absolute beginners : enabling cloud infrastructure security with multi-level security options - Herath, Pushpa (Apress, 2022)
Implement cloud security with Azure security tools, configurations and policies that address the needs of businesses and governments alike. This book introduces you to the most important security solutions available in Azure and provides you with step-by-step guidance to effectively set up security and deploy an application on top of Azure platform services, as well as on top of Azure infrastructure. Author Pushpa Herath begins by teaching you the fundamentals of Azure security. An easy to follow exploration of management groups, subscriptions, management locks and Azure policies further elaborate the concepts underlying Azure cloud security. Next, you will learn about Azure Active Directory (AAD) and the utilization of AAD in application and infrastructure security. Essential aspects of maintaining secure application keys and certificates are further explained in the context of Azure Key Vault. New application security implementations such as Azure configurations and Azure Defender for Azure storage are discussed, as are key platform security factors. Network security groups, gateways, load balancers, virtual networks and firewall configurations are all demonstrated in detail. Finally, you'll learn how to create a much more secure environment through Azure App Service Environment in the context of securing infrastructure. If you want to learn the basics of securing Azure, Azure Cloud Security for Absolute Beginners is for you. After reading the book, you will be able to begin implementing secure cloud solutions with Microsoft Azure. What Will You Learn Get up and running quickly securing Azure Master the basic language of Azure security Understand the security features available in Azure cloud Configure and maintain Azure cloud security features Secure Azure PaaS Services Learn identity and access management options in Azure Cloud Who Is This Book For Cloud engineers, DevOps engineers, software developers and architects who are asked to manage or are involved in the Azure infrastructure management but have not had all that much experience with security.